Private sphere v. public interest. : Constitutional concerns pertaining to preparatory procedure (Academic Journal of Internal Affairs, 2019)
Preparation procedure as a new legal institution defined being a law appeared in the Law XC of 2017 On criminal procedure. Drawing attention on deficiencies of the regulation and on constitutional problems emerges the question: is a limitation of the right to private life without any suspicion adequate to requirements of constitutionality?
Keywords: public interest; private sphere; Hungarian Criminal Procedure Code